1999
DOI: 10.1016/s0893-133x(99)00082-2
|View full text |Cite
|
Sign up to set email alerts
|

Localized Orbitofrontal and Subcortical Metabolic Changes and Predictors of Response to Paroxetine Treatment in Obsessive-Compulsive Disorder

Abstract: Previous positron emission tomography (PET) studies of patients with obsessive-compulsive disorder (OCD) have found elevated glucose metabolic rates in the orbitofrontalPrevious positron emission tomography (PET) studies of obsessive-compulsive disorder (OCD) have found elevated glucose metabolic rates in the orbitofrontal cortex (OFC), anterior cingulate gyrus (AC), caudate nuclei, and thalamus (Baxter et al. 1987(Baxter et al. , 1988Nordahl et al. 1989;Swerdlow 1995; see Saxena et al. 1998 for review) or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
194
1
9

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(225 citation statements)
references
References 54 publications
(58 reference statements)
21
194
1
9
Order By: Relevance
“…Also, these same results were garnered regardless of whether imaging data were obtained during a symptomatic (Provoked) or control (Neutral) state. The inverse correlation between rCBF in OFC and subsequent symptomatic improvement with SRI treatment is consistent with results from three previous studies of OCD employing other SRIs, PET-FDG, and ROI-based analytic methods Saxena et al 1999;Swedo et al 1992). Taken together, these studies underscore the reliability of this finding in OCD, across SRIs, imaging modalities, and data analytic methods.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, these same results were garnered regardless of whether imaging data were obtained during a symptomatic (Provoked) or control (Neutral) state. The inverse correlation between rCBF in OFC and subsequent symptomatic improvement with SRI treatment is consistent with results from three previous studies of OCD employing other SRIs, PET-FDG, and ROI-based analytic methods Saxena et al 1999;Swedo et al 1992). Taken together, these studies underscore the reliability of this finding in OCD, across SRIs, imaging modalities, and data analytic methods.…”
Section: Discussionsupporting
confidence: 88%
“…Based on previous OCD symptom provocation studies (Breiter et al 1996;McGuire et al 1994;Rauch et al 1994), we predicted activation in OFC, anterior cingulate cortex, and the caudate nucleus. Based on previous imaging studies of predictors of treatment response in OCD Rauch et al 2001b;Saxena et al 1999;Swedo et al 1992), we predicted correlations in OFC and PCC. Loci exhibiting effects of comparable statistical significance are also reported for completeness, and to obviate bias.…”
Section: Pet Predictors Of Fluxoamine Response In Ocd 785mentioning
confidence: 99%
See 1 more Smart Citation
“…In our patients with OCD, the LD of the right primary auditory cortex (tangential dipole) was associated with both serotonin and dopamine transporter availabilities. Brain functional abnormalities in patients with OCD have repeatedly been shown in imaging and neurophysiological studies, and many of these investigations revealed more pronounced right-sided alterations (Baxter et al, 1992;Saxena et al, 1999;Saxena and Rauch, 2000). This could explain that in our study only the right LD, representing the right primary auditory cortex, revealed significant correlations with the imaging data.…”
Section: Discussionsupporting
confidence: 63%
“…Current knowledge from functional and structural neuroimaging emphasizes abnormalities of fronto-striatalthalamic-cortical circuits and orbitofronto-striato-thalamic circuits in the pathophysiology of OCD [9,10] . In this context, structural imaging studies have implicated the pathology of basal ganglia and frontal regions [11] .…”
Section: Key Brain Regionsmentioning
confidence: 99%